A novel hybrid scale for the assessment of cognitive and executive function: The Free‐Cog. (16th November 2020) - Burns, Alistair; Harrison, Judith R.; Symonds, Catherine; Morris, Julie
Abstract: Background: Scales measuring cognitive and executive functions are integral to the assessment and management of patients with suspected cognitive impairment. Some of the most commonly used cognitive tests are now subject to copyright restrictions. Furthermore, no existing scale assesses both executive and cognitive abilities. Aims: We aimed to develop and validate a novel hybrid scale for use in clinical practice which integrate measures of cognition and executive abilities ('Free‐Cog'). Methods: The instrument was devised through a national collaboration including health professionals, those with lived experience of dementia and researchers. Following ethics committee approval, the Free‐Cog was assessed in 25 real‐world clinical settings across England, Wales and Scotland. It was compared to three other cognitive tests routinely administered in clinical practice: the Mini‐Mental State Examination (MMSE), the Montreal Cognitive Assessment (MOCA), and the Addenbrooke's Cognitive Examination (ACE). Results: The Free‐Cog was tested in 960 patients with clinical diagnoses of dementia, Mild Cognitive Impairment (MCI), and normal controls. Similar to the MMSE, MOCA and ACE, it discriminated well between the three groups ( p < 0.001). It correlated well with the other instruments. Using a receiver operating characteristic curve analysis, Free‐Cog achieved an Area Under Curve of 0.94 for dementia versus controls, 0.80 for MCI versus controls and 0.77 for dementia versus MCI. A version of the tool adapted for telephone consultation, the Tele Free‐Cog, also discriminated well between patient groups. Conclusions: Free‐Cog is a non‐proprietary, empirically derived, concise assessment. Uniquely, it combines cognitive and executive function questions in the one instrument. It could be used to inform the assessment of people presenting with cognitive impairment and is available to anyone interested in trialling it.